THE IMPACT OF DIGITALIZATION ON ECONOMIC MANAGEMENT THEORY AND PRACTICE: ANALYSIS AND PROSPECTS IN THE GLOBAL MARKETPLACE - Yuli Alam; Irian Nasri, Efniar, Violeta (Adisam Publisher, 2024)
In an ever-evolving information age, digitalization has reshaped the economic management landscape, opening up new opportunities while presenting a unique set of challenges. This literature review aims to explore the influence of digitalization on economic management theory and practice, highlighting the changes taking place in the way companies conduct their operations and interact with global markets. The study adopts an analytical approach to the existing literature according to the context of the research discussed. The results show that digitalization has catalyzed innovations in data collection and analysis, introduced automation and increased operational efficiency, and opened pathways for personalization of products and services. These factors have collectively enhanced companies' competitiveness and ability to operate on a global scale. However, these shifts also pose significant challenges, including cybersecurity concerns, the need for labor skills transfer, and the digital divide between different economic actors. Moreover, the findings emphasize the need for adaptive regulatory frameworks that can support cross-border cooperation while ensuring ethical and sustainable practices.